Livro-texto para olimpíadas de astronomia - Silva Júnior, Isaías Batista da (2022)
This dissertation aims to explain how the use of an adequate teaching material can be able to arouse interest in Astronomy learning, correct concepts erroneously acquired during the stages of Elementary and High School and prepare students to participate in Olympiads of Astronomy. Science Olympiads have become another way of accessing public higher education and the lack of didactic material and teacher training in Astronomy can leave gaps in learning. The book Astronomy Guide - For the Brazilian Astronomy and Astronautics Olympiad (OBA) and National Science Olympiad (ONC) was developed to present the main contents covered in both Olympiads in a simple way. The writing of the theoretical part sought to keep close to the language present in the tests of Elementary School - Final Years of the OBA of the last years so that the student can use the Guide with the instruction of a teacher or even in their individual study.